2000
DOI: 10.1177/074193250002100402
|View full text |Cite
|
Sign up to set email alerts
|

Block Scheduling and Inclusion in a High School

Abstract: This investigation used qualitative methods to examine the impact of the implementation of a block schedule on an inclusive high school program that had been working successfully for several years. Data were collected using a series of classroom observations and interviews with seven teachers of students with disabilities and seven general education teachers who worked as co-teachers in inclusive classrooms. A constant comparative method of data analysis (Glaser & Strauss, 1967) was used to identify themes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…According to Payne and Jordan's (1996) study on the instructional impact of AB block scheduling, "teachers reported that they enjoyed having more time to give students individual assistance; opportunities to get to know the students personally; time for more creative and meaningful student work; and the ability to structure a full lesson" (p. 18). Thus, these advantages of an 85-minute block period led to a less stressful and more flexible classroom climate (Payne & Jordan, 1996;Weller & McLeskey, 2000). As a result, supportive teachers working under this type of block scheduling develop curricula focused on cooperative learning exercises to take advantage of the longer blocks of time (Weller & McLeskey, 2000).…”
Section: Alternate Day Block (Ab) Planmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Payne and Jordan's (1996) study on the instructional impact of AB block scheduling, "teachers reported that they enjoyed having more time to give students individual assistance; opportunities to get to know the students personally; time for more creative and meaningful student work; and the ability to structure a full lesson" (p. 18). Thus, these advantages of an 85-minute block period led to a less stressful and more flexible classroom climate (Payne & Jordan, 1996;Weller & McLeskey, 2000). As a result, supportive teachers working under this type of block scheduling develop curricula focused on cooperative learning exercises to take advantage of the longer blocks of time (Weller & McLeskey, 2000).…”
Section: Alternate Day Block (Ab) Planmentioning
confidence: 99%
“…Thus, these advantages of an 85-minute block period led to a less stressful and more flexible classroom climate (Payne & Jordan, 1996;Weller & McLeskey, 2000). As a result, supportive teachers working under this type of block scheduling develop curricula focused on cooperative learning exercises to take advantage of the longer blocks of time (Weller & McLeskey, 2000). Payne and Jordan (1996) also found that teachers were positive about the way classes were scheduled, staff development, and planning time afforded by an AB schedule.…”
Section: Alternate Day Block (Ab) Planmentioning
confidence: 99%
See 1 more Smart Citation
“…If these students are seen in a holistic way, then their happiness or unhappiness at school must be of utmost importance to the school and its teachers, as this affects the quality of all relationships within the school community. This has implications on all levels but particularly on the organisational structure of secondary schools which delineates teachers by the subjects they teach and students by their results in a particular subject without reference to any other information (Weller & McLeskey, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers were able to get to know their students personally and had more time to give students individual attention (Payne & Jordan, 1996;Weller & McLeskey, 2000). In addition, because there were fewer class changes, there was more time available for academic instruction and fewer opportunities for discipline issues to arise (Evans et al, 2002;O'Neil, 1995;Zepeda & Mayers, 2006).…”
Section: Advantages Of Block Schedulingmentioning
confidence: 99%